SCALAR COSMOLOGICAL PERTURBATIONS OF PRESSURELESS MATTER IN THE BRANEWORLD MODEL - Viznyuk, A. V.; Shtanov, Yu. V. (Одеські астрономічні публікації, 2012)
We present a complete set of differential equations describing the evolution of scalar cosmological perturbations of pressureless matter on the brane in the general case where the action of the model contains the induced-curvature term as well as the cosmological constants in the bulk and on the brane.